Drawing Inferences on The Basis of Level of Statistical Tools Used in Data Analysis - Karki, Murari (Interdisciplinary Journal of Management and Social Sciences, 2021)
Statistics is the science which deals with the collection, organisation, tabulation, manipulation, analysis and interpretation of observed results (Winters R, Winters A, Amedee RG. Statistics: A brief overview. Ochsner J. 2010;10:213-6.).Using all the statistical procedure, we draw some inferences about population parameter from the study sample. Before drawing inferences about population parameters, we use different levels of statistical tools. This article is meant to provide some information to reader about various statistical methods that are useful for the process of making inferences about parameters. This article is focused on the various levels of statistical tools, difference between descriptive and inferential statistics and various test statistic to make conclusion about population parameters.